ТЕРАПИЯ ТРЕВОЖНЫХ РАССТРОЙСТВ У ПАЦИЕНТОВ С СЕРДЕЧНО-СОСУДИСТЫМИ ЗАБОЛЕВАНИЯМИ (ОПЫТ ПРИМЕНЕНИЯ АФОБАЗОЛА) - В. Э. Медведев (Архивъ внутренней медицины, 2013)
According to modern researches data, patients with cardiovascular diseases often suffer from symptoms of anxiety-phobic, panic, somatoform disorders and hypochondria. One of the most common signs of psychopathological disorders in patients with cardiovascular diseases are anxiety symptoms. Development and introduction into clinical practice of new Russian anxiolytic Afobazol had opened new perspectives in the treatment of those patients.